Mitochondrial Dysfunction and Damage Associated Molecular Patterns (DAMPs) in Chronic Inflammatory Diseases - Dela Cruz, Charles S. (Mitochondrion, 2017)
Inflammation represents a comprehensive host response to external stimuli for the purpose of eliminating the offending agent, minimizing injury to host tissues and fostering repair of damaged tissues back to homeostatic levels. In normal physiologic context, inflammatory response culminates with the resolution of infection and tissue damage response. However, in a pathologic context, persistent or inappropriately regulated inflammation occurs that can lead to chronic inflammatory diseases. Recent scientific advances have integrated the role of innate immune response to be an important arm of the inflammatory process. Accordingly, the dysregulation of innate immunity has been increasingly recognized as a driving force of chronic inflammatory diseases. Mitochondria have recently emerged as organelles which govern fundamental cellular functions including cell proliferation or differentiation, cell death, metabolism and cellular signaling that are important in innate immunity and inflammation-mediated diseases. As a natural consequence, mitochondrial dysfunction has been highlighted in a myriad of chronic inflammatory diseases. Moreover, the similarities between mitochondrial and bacterial constituents highlight the intrinsic links in the innate immune mechanisms that control chronic inflammation in diseases where mitochondrial damage associated molecular patterns (DAMPs) have been involved. Here in this review, the role of mitochondria in innate immune responses is discussed and how it pertains to the mitochondrial dysfunction or DAMPs seen in chronic inflammatory diseases is reviewed.